(untitled) (Sebha University Conference Proceedings, 2024)
This paper presents an analytical method for solving fuzzy linear differential equations with fuzzy initial conditions. The study investigates three distinct cases based on the signs of the coefficients in the fuzzy differential equations. The proposed method relies on transforming the fuzzy differential equation into an ordinary differential equation using the Fuzzy Centre Method (FCM). Subsequently, the ordinary differential equation is solved using a standard method. Finally, the solution is rewritten using the fuzzy membership function μ(x) to obtain the solution of the fuzzy linear differential equation. The method is illustrated through illustrative examples.